On a Stochastic Trotter Formula with Application to Spontaneous Localization Models - Dürr, D; Hinrichs, G; Kolb, M (2011)
We consider the relation between so called continuous localization models-i.e. non-linear stochastic Schrödinger evolutions-and the discrete GRW-model of wave function collapse. The former can be understood as scaling limit of the GRW process. The proof relies on a stochastic Trotter formula, which is of interest in its own right. Our Trotter formula also allows to complement results on existence theory of stochastic Schrödinger evolutions by Holevo and Mora/Rebolledo. © 2011 Springer Science+Business Media, LLC.